2020
DOI: 10.1111/acps.13164
|View full text |Cite
|
Sign up to set email alerts
|

Trends in suicide death risk in transgender people: results from the Amsterdam Cohort of Gender Dysphoria study (1972–2017)

Abstract: Objective: This study explored the overall suicide death rate, the incidence over time, and the stage in transition where suicide deaths were observed in transgender people. Methods: A chart study, including all 8263 referrals to our clinic since 1972. Information on death occurrence, time, and cause of death was obtained from multiple sources. Results: Out of 5107 trans women (median age at first visit 28 years, median follow-up time 10 years) and 3156 trans men (median age at first visit 20 years, median fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 28 publications
2
41
0
4
Order By: Relevance
“…The finding concerning LGBTQIA* individuals as one group was expected (Hypothesis 2) and is in line with previous empirical work [ 21 ]. Research in this field is growing, and the vast majority of studies report significantly poorer well-being and mental health in individuals with minoritized sexual and/or gender identities when compared with heterosexual and cisgender individuals [ 44 47 ]. A recent systematic literature review of N = 77 studies reported higher general distress, depressive symptoms, anxiety, suicidality as well as exposure to trauma and substance abuse among LGBTQIA* individuals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding concerning LGBTQIA* individuals as one group was expected (Hypothesis 2) and is in line with previous empirical work [ 21 ]. Research in this field is growing, and the vast majority of studies report significantly poorer well-being and mental health in individuals with minoritized sexual and/or gender identities when compared with heterosexual and cisgender individuals [ 44 47 ]. A recent systematic literature review of N = 77 studies reported higher general distress, depressive symptoms, anxiety, suicidality as well as exposure to trauma and substance abuse among LGBTQIA* individuals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Wiepjes et al, they find an increased risk of suicide in the studied transgender population compared with the general population (1). They report 49 suicides out of 5107 cases.…”
mentioning
confidence: 85%
“…In the study, ‘Trends in suicide death risk in transgender people: Amsterdam Cohorte Gender dysphoria study’ Wiepjes et al investigate the risk of suicide in a large Dutch cohort of transgender people in the period between 1972 and 2017 (1). They find that transwomen have a higher overall suicide death risk than transmen and that in the period from 2013 to 2017, the mean number of suicides per year was higher in the transgender population than in the overall Dutch population.…”
mentioning
confidence: 99%
“…It looked at the overall suicide death rate in a total of 8,263 trans-identifying men and women, including adolescents and children. Seventy percent of those who had committed suicide were in active treatment with near equal distribution of deaths across the different phases of treatment (Wiepjes et al 2020). Another study published in October, 2019, evaluated the mental health treatments of 2,679 individuals in the Swedish National Patient Register diagnosed with gender incongruence.…”
Section: Box 4: Contextual Features—implications For Individuals Families Society and The Profession Of Medicinementioning
confidence: 99%